No genetic causal association between systemic lupus erythematosus and COVID-19 - Xu, Shu-Zhen; Wang, Zhi-Xin; Fang, Xi; Chen, Cong; Yang, Xiao-Ke; Shuai, Zong-Wen; Tao, Sha-Sha (Frontiers in Immunology, 2023)
Objective Emerging evidence show that the prevalence of Coronavirus disease 2019 (COVID-19) in patients with systemic lupus erythematosus (SLE), the prototype of autoimmune disorders, is increased compared to the general population. However, the conclusion is inconsistent and the causal relationship between COVID-19 and SLE remains unknown. Methods In this study, we aimed to evaluate the bidirectional causal relationships between COVID-19 and SLE by bidirectional Mendelian randomization (MR) analysis, including MR-Egger, weighted median, weighted, and inverse variance weighting (IVW) mode. Results The results of IVW showed a negative effect of SLE on severe COVID-19 (OR= 0.962, P= 0.040) and COVID-19 infection (OR= 0.988, P= 0.025), which disappeared after Bonferroni correction. No causal effect of SLE on hospitalization COVID-19 was observed (OR= 0.983, P= 0.148). In the reverse analysis, no causal effects of severe COVID-19 infection (OR= 1.045, P= 0.664), hospitalization COVID-19 (OR= 0.872, P= 0.109) and COVID-19 infection (OR= 0.943, P= 0.811) on SLE were found. Conclusion The findings of our bidirectional causal inference do not support a genetically predicted causal relationship between SLE and COVID-19, thus their association observed in previous observational studies may be caused by confounding factors.